2016
DOI: 10.4081/or.2016.6384
|View full text |Cite
|
Sign up to set email alerts
|

Bone transport for limb reconstruction following severe tibial fractures

Abstract: A common treatment of tibial defects especially after infections is bone transport via external fixation. We compare complications and outcomes of 25 patients treated with a typical Ilizarov frame or a hybrid system for bone reconstruction of the tibia. Average follow up was 5.1 years. Particular interest was paid to the following criteria: injury type, comorbidities, development of osteitis and outcome of the different therapies. The reason for segmental resection was a second or third grade open tibia fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
1
17
0
1
Order By: Relevance
“…In 6 of the 27 studies, infected and noninfected CSBD were mixed [19, 25, 2932, 39]. Eighteen studies included only infected tibial CSBD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 6 of the 27 studies, infected and noninfected CSBD were mixed [19, 25, 2932, 39]. Eighteen studies included only infected tibial CSBD.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, when the mean complication per patient was evaluated, it was found that 1 out of 27 did not have sufficient information [32] (Table 2). Two of the remaining 26 studies classified complications according to the Paley system.…”
Section: Resultsmentioning
confidence: 99%
“…In the treatment of long bone pathologies, there are some processes that keep the length of the limb (e.g., bone transport, bone healing, or tissue engineering [ 30 , 38 , 40 ]) during the regeneration process and others that imply its modification (e.g., bone shortening or lengthening [ 41 , 42 ]). The selection of the proper treatment depends on the clinical pathology of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…High energy accompanied with open injury leads to severe bone and soft tissue contamination which requires thorough debridement [2] , on the contrary, repeated debridement will cause more serious bone loss and defects which result in further complicated situations such as chronic infections, soft tissue defects, joint contractures, and lower limb deformities or discrepancy [3][4][5] . At present, Ilizarov bone transport technique has become the preferred treatment option to simultaneously solve this series of problems [6] .…”
Section: Introductionmentioning
confidence: 99%